Gestão do patrimônio cultural (pelos) Guarani enquanto usufruto das terras por eles tradicionalmente ocupadas e indispensáveis à sua reprodução social - Silva, Dario Luiz da (2015)
The objective of this master thesis is to provide management advice for the Cultural Heritage of the remains of São Miguel Arcanjo that address the demand of the indigenous Guarani community of São Miguel das Missões, under the professional master thesis in Cultural Heritage. To achieve the goal, the first chapter deals with the cultural heritage of São Miguel Arcanjo and the indigenous issue, considering the conflicting dynamics that constitute the cultural space. For this purpose, are treated in a detailed way the symbolic mediations involving the theme and also the eurocentric assumption – as a category of analysis – predominant approaches to the question, by the State, prior to the brazilian Constitution of 1988. The second chapter discusses the changes on state approach that materialized in the Constitution of 1988, the open possibilities to the recognition of indigenous rights and the problems related to their effective implementation. The third chapter is reserved to the discussion of ethnic tourism and alternatives to physical and cultural reproduction of indigenous communities, where similar experiences will be analyzed. As a product of the master thesis, it was drafted a proposal whose purpose is to contribute to the realization of indigenous demands of the Aldeia Alvorecer. The methodology consists of making literature review, document analysis, cartographic analysis, collection and treatment of secondary and primary data.